Gestión de ventas de las subdistribuidoras de cerveza pílsener del Cantón Babahoyo y su impacto en la rentabilidad, Períodos 2013-2014, Plan estratégico de marketing. - Márquez Cabezas, Omar Benigno (2016)
Sales management has a strategic role in the company and its implementation is a challenge, the growing concentration of distribution channels, the increased globalization of markets, are some trends driving companies to invest substantial resources to organize adequately the sales function, and design and implement a successful sales process. This research was conducted in the sub-distributors of pilsener the canton Babahoyo, aimed at improving the processes of sales, the primary objective of the research is to evaluate the sales management of the sub-distributors Pilsener beer Canton Babahoyo and its impact on profitability, today these sub-distributors do not have the return expected by their level of sales is not expected, and there is not yet market access for lack of sales strategies. The methodology used in this investigation it will based on the application of methods and research techniques, for which questionnaires of questions designed whose purpose is to have a closer relationship with the party involved in the process of marketing the product, the results show that the profitability of sub-distributors is at an average level for the poor service provided to its customers and the lack of publicity, so it is proposed to implement a marketing plan and improve their sales.